SIMBOLISASI BENANG TRI DATU SEBAGAI KOMUNIKASI KULTURAL UMAT HINDU BERDASAR TELAAH TEORI KOMUNIKASI - Paramita, Eka Putri (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2018)
Communication is one of the most important aspects but also complex in human life. Every human being is using theory to guide the understanding of things and give a decision on what action should be performed. Based on an understanding of this is becoming interesting to see in more depth about the phenomenon of the use of the thread tridatu in the study of communication theory. The number of user threads tridatu seems to be a growing trend on Hindus. The question then is how the phenomenon of symbolizing the thread this has been analyzed with tridatu using the theory of communication. Among them are the symbolic interaction theory, the theory of self-disclosure and the theory of social interaction. The results showed that the thread symbolizing tridatu was described based on the perception of the whole of the respondents who had researchers meet. each of the respondents giving different perception that found against the use of FLOSS tri researchers analyze then datu opinion the respondents using the first communication theory, beginning with the symbolic Interaction theory based on This theory can be seen that the use of threads on the whole tridatu almost Hindus indicates that the thread Tridatu in Hindus have experienced significant shifts in meaning. From which a marker that someone has completed implementing the ceremony. To develop into one of the means of communication, which indirectly connects between Hindus who are one with the other. Then the second, the theory of self-disclosure, after the communication formed, Hindus who felt they have in common because it uses Tridatu yarns will felt has a personal affinity. And there is trust. And thirdly, that the theory of the construction of identity-based on this theory can be described that the use of the thread tridatu in the life of a days will indirectly construct an identity. The identity of the user stating if its was a Hindu.